Improved reference image encryption methods based on 2k correction in the integer wavelet domain - Tuncer, Turker; Dogan, Sengul; Tadeusiewicz, Ryszard (1947- ); Pławiak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Many visually meaningful image encryption (VMIE) methods have been proposed in the literature using reference encryption. However, the most important problems of these methods are low visual quality and blindness. Owing to the low visual quality, the pre-encrypted image can be analyzed simply from the reference image and, in order to decrypt nonblind methods, users should use original reference images.
Keywords: visually meaningful image encryption; 2k correction; discrete wavelet transform; least significant bits embedding